2020
DOI: 10.1186/s13148-020-0810-2
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxymethylcytosine signatures in circulating cell-free DNA as diagnostic and predictive biomarkers for coronary artery disease

Abstract: Background: The 5-hydroxymethylcytosine (5hmC) DNA modification is an epigenetic marker involved in a range of biological processes. Its function has been studied extensively in tumors, neurodegenerative diseases, and atherosclerosis. Studies have reported that 5hmC modification is closely related to the phenotype transformation of vascular smooth muscle cells and endothelial dysfunction. However, its role in coronary artery disease (CAD) has not been fully studied. Results: To investigate whether 5hmC modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that 5hmC-modified loci can serve as excellent biomarkers for the diagnosis and prognosis of human diseases including cancer [19][20][21][23][24][25][26] . These data suggest that 5hmC may mark specific genes or promoter/enhancers in disease samples that undergo concerted changes representative of the disease pathogenesis in question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that 5hmC-modified loci can serve as excellent biomarkers for the diagnosis and prognosis of human diseases including cancer [19][20][21][23][24][25][26] . These data suggest that 5hmC may mark specific genes or promoter/enhancers in disease samples that undergo concerted changes representative of the disease pathogenesis in question.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 5hmC modifications co-localize with gene bodies and enhancers are known to mark for transcription activation 6,17,18 . Notably, in several recent studies, the 5hmC-modified loci have been shown to serve as informative biomarkers for a variety of human cancers and other complex diseases [19][20][21][22][23][24][25][26] . Interestingly, two early studies that investigated the 5hmC in circulating cell-free DNA from patients with solid tumors suggested that 5hmC had the potential to be specific biomarkers for human cancers arising from different tissue origins 19,20 .…”
mentioning
confidence: 99%
“…The DNA modification of 5-hydroxymethylcytosine (5hmC) is a significant DNA epigenetic alteration that affects global gene expression and is involved in tumors, neurodegenerative diseases, and atherosclerosis [12][13][14]. Genome-wide 5hmC distributions and dynamics in various human tissues have shown that it is mainly enriched in the gene body region and has a potential role in gene regulation in mammalian development and cell differentiation [15]. 5hmC was recently determined to be a potential cfDNA biomarker for nonsmall-cell lung cancer and esophageal cancer [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In the detection of 5hmC, Han et al (2016) developed 5hmC selective chemical labeling technology (hmC-Seal) by combining chemical synthesis technology with modern biological technology. It opens the door for the research and clinical transformation of 5hmc ( Gao et al, 2019 ; Dong et al, 2020 ). However, this method is unable to obtain specific 5hmc modification sites at a single-base level.…”
Section: Current Methods For Detecting Dna and Rna Modificationsmentioning
confidence: 99%